Parametric Rule-Based Intelligent System (PRISM) for Design and Analysis of High-Strength Separable Microneedles - Sanghwi Ju; Seung-hyun Im; Kyungsun Seo; Junhyeok Lee; Seokjae Kim; Tongil Park; Taeksu Lee; Byungjeon Kang; Jayoung Kim; Ryong Sung; Jong-Oh Park; Doyeon Bang (Micromachines, 2025)
Transdermal microneedle systems have received great attention due to their minimally invasive way of delivering biomolecules through the skin with reduced pain. However, designing high-strength separable microneedles, which enable easy skin penetration and easy patch detachment, is challenging. Here, we present a Parametric Rule-based Intelligent System (PRISM), which generates the design of and analyzes high-strength separable microneedles. The PRISM platform integrates parametric 3D modeling, geometry-based structural analysis, and high-resolution micro-3D printing for the creation of high-strength separable microneedles. We fabricated prototype microneedle arrays via microscale stereolithographic printing (pµSL) and demonstrated separation of microneedle tips in a skin-mimicking phantom sample. Mechanical testing showed that the suggested design achieved 2.13 ± 0.51 N axial resistance and 73.92 ± 34.77 mN shear fracture force; this surpasses that of conventional designs. Finally, an experiment using a skin-mimicking artificial phantom sample confirmed that only the PRISM-designed separable microneedles could have been inserted and separated at the target depth, whereas conventional designs failed to detach. This approach addresses the development of microneedle systems, which achieve both robust skin phantom penetration and reliable separable delivery, presenting an efficient development tool in transdermal drug delivery technology.